Fermented barley extract supplementation ameliorates metabolic state in stroke-prone spontaneously hypertensive rats. Issue 11 (2nd November 2015) - ,; Shirakawa, Hitoshi; Giriwono, Puspo E; Oguchi, Kazuki; Ueda, Kazuma; Hokazono, Hideki; Hiwatashi, Kazuyuki; Takahashi, Saori; Sato, Shoko; Komai, Michio
Abstract: We studied the effects of fermented barley extract P (FBEP) in stroke-prone spontaneously hypertensive rats (SHRSP). Male 10-week-old SHRSP were divided into three groups that were fed: an AIN-93M diet (control), a low dose of FBEP (4 g/kg; FBEP1), and a high dose of FBEP (20 g/kg; FBEP2) for three weeks. Hypertension was significantly improved by the use of FBEP supplementation. The FBEP diet improved plasma triglyceride, insulin sensitivity, enhanced plasma catalase, and superoxide dismutase activities, and decreased plasma 8-hydroxy-2′-deoxyguanosine levels. In addition, the FBEP diet upregulated hepatic antioxidative genes and modulated Nrf2 protein levels in the liver. Furthermore, a single oral dose of FBEP (2 g/kg body weight) was able to lower blood pressure in SHRSP. In conclusion, our data suggest that increased expression of hepatic antioxidative genes and modulation of Nrf2 may play a role in the regulation of metabolic diseases in SHRSP consuming a FBEP diet. Graphical abstract: : Chronic administration of fermented barley extract significantly reduces systolic blood pressure in SHRSP.